Review. Anthony Traill 2018. A Trilingual !Xóõ Dictionary. !Xóõ – English – Setswana - Fehn, Anne-Maria (AAeO - Afrikanistik-Aegyptologie-Online, 2018)
For any scholar with an interest in Southern African ‘Khoisan’, it is almost mandatory to become familiar with the works of Anthony Traill (1939-2007). Few linguists have matched the impact and scope of his studies on the phoneme inventories, phonological characteristics and other aspects of the languages now grouped into the Kx’a, Tuu and Khoe-Kwadi families (Güldemann 2014). Apart from his invaluable contributions to comparative ‘Khoisan’ studies, Traill is probably best remembered as the unchallenged specialist on the northeasternmost Taa variety subsequently referred to as (East) !Xóõ. Starting from 1969, he undertook innumerable field trips to the Lone Tree-Kagcae area in Botswana and, with the help of his !Xóõ assistants, collected an extensive corpus of data on their language and culture which was to result in three major monographic publications.